2005
DOI: 10.1002/cncr.21212
|View full text |Cite
|
Sign up to set email alerts
|

Infections in children and young adults with bone malignancies undergoing limb‐sparing surgery

Abstract: Objective The reduced risk for Alzheimer's disease (AD) in high‐educated individuals has been proposed to reflect brain cognitive reserve, which would provide more efficient compensatory mechanisms against the underlying pathology, and thus delayed clinical expression. Our aim was to find possible differences in brain amyloid ligand 11C‐labeled Pittsburgh Compound B ([11C]PIB) uptake and glucose metabolism in high‐ and low‐educated patients with mild AD. Methods Twelve high‐educated and 13 low‐educated patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
1
31
0
1
Order By: Relevance
“…These secondary complications occurred over time, and while revision surgery can be successful in many, some patients experienced further complications and implant failure, an observation noted by others [4,6,13,20,21,24]. Clearly, further efforts in understanding the causes of complications and strategies to prevent them could lead to substantial improvements in implant survival.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These secondary complications occurred over time, and while revision surgery can be successful in many, some patients experienced further complications and implant failure, an observation noted by others [4,6,13,20,21,24]. Clearly, further efforts in understanding the causes of complications and strategies to prevent them could lead to substantial improvements in implant survival.…”
Section: Discussionmentioning
confidence: 89%
“…While others have reported specifically on these complications and potential methods of salvage following complications of endoprosthetic reconstruction [6,12,13,20,21,23,24], little has been published regarding the incidence of complications seen with extended followup or how patients fared longitudinally after undergoing salvage of a complication. Some of these studies concentrated only on infection [6,12,13] while others reviewed the major types of complications without discussing their time frame, concentrating on survivor analysis rather on complications analysis [1,8,11,14,21,23,24]. We previously reported early results of a cohort of 82 patients who underwent segmental endoprosthetic replacement for sarcoma of bone, which showed a prosthetic survival rate of 83% at 5 years and 67% at 10 years [17].…”
Section: Introductionmentioning
confidence: 95%
“…Complex arthroplasty and reconstruction procedures, large implants, greater surgical exposure and soft tissue dissection or resection, lack of soft tissue coverage, malignant tumors, previous surgery, long operating times, radiation therapy and chemotherapy, malnutrition, anemia, advanced age, diabetes mellitus, obesity, skin disease, and joint disease are the major factors associated with higher infection rates of megaprostheses compared with conventional arthroplasties [11,14,24,26,27]. Surgical risk factors for infection include revision procedures such as bushing exchange, patellar resurfacing, invasive lengthening of expandable tumor prostheses in children, cemented fixation, and joint as opposed to intercalary prosthetic reconstructions [3,14,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of infection of megaprostheses has been comparable to that associated with other methods of reconstruction following limb salvage surgery, such as autograft or allograft reconstruction [8][9][10]. However, it remains five-to ten-fold higher than the rates following routine total joint arthroplasties [11,12].…”
mentioning
confidence: 98%
“…Late prosthetic infections are associated with poor results when treated by lavage, debridement, and prolonged antibiotics administration 67 ; therefore, removal of infected prosthesis either as 1-or 2-stage procedure or an amputation becomes necessary. 42,[68][69][70][71] The reported success rate of eradicating infection with amputation ranges from 98% to 100%, 72% to 91% with 2-stage revision, and 42% with 1-stage revision. 70 However Allison et al 36 reported success rate of 42% with irrigation and debridement procedures alone (without any component exchange), 70% with single-stage irrigation and debridement procedure with the addition of modular component exchange and varying degrees of suppressive antibiotics, and in contrast to other studies formal two-staged implant removal, antibiotic spacer placement with subsequent reimplantation was associated with 62%.…”
Section: Custom-made Megaprosthesismentioning
confidence: 99%